Um caminho de aprendizagem rumo à profissão docente: sinergias entre professor e alunos - Silvano Roberto Bravo Freitas (2024)
The Professional school placement is part of the 2nd year of the Master's Degree in Teaching Physical Education in Basic and Secondary Education at the Faculty of Sport of the University of Porto, and this document is essential for completing the cycle of studies. It refers to the personal and professional development of a preservice teacher during a school year in the context of supervised teaching practice, and includes personal experiences, difficulties and strategies inherent to the stage. Throughout the document, the aim is to present the context and environment in which the practice was carried out, showing the various moments and main themes that influenced teaching practice. As this is a document that describes a cycle, personal considerations are implicit in this report, based on scientific support in the field of physical education. The approach to socioconstructivist theories, the relevance of physical education and the problem of assessment are prominent themes. The activities developed in relation to the school and the environment are summarised, showing the involvement, commitment, sense of belonging and pride in the teaching profession and its specificities. The structure of the document also includes an applied study carried out in the student intern's resident class, related to the application of a hybrid model in futsal and its possible influence on the number of actions and the success rate of actions in the context of the game. At the end of the document, there are final considerations about the journey and future prospects.